Adapted pricing scheme for the integration of vehicle-to-grid into the energy system - Teske, Franz; Fehrle, Adrian; Praß, Julian; Franke, Jörg (11th International Electric Drives Production Conference (EDPC), 2021)
Temporarily high electricity demand resulting from simultaneous charging of many electric vehicles (EVs) require massive expansion of the future grid infrastructure. Using EVs in a way that serves the power system in such by contributing to peak shaving, valley filling, and flattening the load curve of the grid would help to reduce the cost of grid expansion. Based on the current market design, grid-serving bidirectional charging of EVs is still uneconomical for the EVs owners in Germany since it is burdened with various levies, taxes, and fees. We propose an adapted pricing scheme for bidirectional charging that incentivizes a system-serving behavior. For this purpose, we develop a mixed-integer linear optimization model that considers different types of electricity use in the EVs. Based on a simulation, we show that bidirectional charging can generate significant profits under the condition that the system-serving electricity quantities are billed without levies, taxes, and fees or if the EVs are treated like other storage units operating on the electricity market. The analysis shows that bidirectional grid interactions are particularly worthwhile for parking situations at residential properties, especially with long parking times on weekends, high electricity consumption and when taking advantage of volatile intraday prices.<br
Keywords: electric vehicle; linear programming; pricing; charging and discharging schedule; vehicle to grid